Sulfur-Mediated ipso-Cyclization of 4-(p-Methoxyaryl)alk-1-ynes Leading to 3-Thiospiro[4.5]deca-1,6,9-trien-8-ones - Han, Meng; Li, Pingfan (Synlett, 2024)
A new method for the intramolecular electrophilic ipso-cyclization of alkynes with triflic anhydride-activated sulfoxides, followed by demethylation with triethylamine in one pot, is described for the synthesis of 3-thiospiro[4.5]-decatrienones in moderate to good yields. This method provides a facile strategy for assembling the sulfur-substituted spirocyclic compounds.
Keywords: alkynes; sulfoxides; ipso-cyclization; spiro compounds; dearomatization